2023
DOI: 10.3389/fphar.2023.1143784
|View full text |Cite
|
Sign up to set email alerts
|

The difference in mean arterial pressure induced by remimazolam compared to etomidate in the presence of fentanyl at tracheal intubation: A randomized controlled trial

Abstract: Background: Combined use of hypnotic and opioids during anesthesia inductions decreases blood pressure. Post-induction hypotension (PIHO) is the most common side effect of anesthesia induction. We aimed to compare the difference in mean arterial pressure (MAP) induced by remimazolam with that induced by etomidate in the presence of fentanyl at tracheal intubation.Methods: We assessed 138 adult patients with American Society of Anesthesiologists physical status I–II who underwent elective urological surgery. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Unlike the infusion of propofol and midazolam, which are known to reduce blood pressure in a dose-dependent manner [23,24], continuous infusion of remimazolam demonstrated no dose-cumulative effect on blood pressure in the present case. This observation aligns with the findings of previous studies involving patients without obesity receiving remimazolam infusion, where changes in blood pressure and heart rate were maintained within 20% of the baseline values during anesthesia induction [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the infusion of propofol and midazolam, which are known to reduce blood pressure in a dose-dependent manner [23,24], continuous infusion of remimazolam demonstrated no dose-cumulative effect on blood pressure in the present case. This observation aligns with the findings of previous studies involving patients without obesity receiving remimazolam infusion, where changes in blood pressure and heart rate were maintained within 20% of the baseline values during anesthesia induction [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…However, the evidence comparing remimazolam and etomidate for induction of general anesthesia is conflicting. Huang et al [ 26 ] found that the remimazolam group had a higher incidence of PIHO and a lower heart rate during induction than the etomidate group. However, some studies have found that low-dose remimazolam is hemodynamically more stable and has fewer adverse effects than etomidate in noncardiac and cardiac surgery [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%